ANALISIS TINGKAT PENYIMPANAN SENYAWA KARBON (C-Stock) PADA VEGETASI HUTAN MANGROVE BERDASARKAN PERBEDAAN SUBTRAT DI PULAU SAPARUA KABUPATEN MALUKU TENGAH - Patriks Sitaniapessy; Pamela Mercy Papilaya (Program Studi Pendidikan Biologi FKIP Unpatti, 2018)
Background: Analysis of the level of storage of Carbon compounds (C-Stock) on mangrove forest vegetation based on differences in substrate on Saparua Island, Central Maluku Regency. This study aims to determine the amount of carbon content and the difference in carbon content stored in mangrove forests. Method: This study used a survey method through direct observation in the field and analysis of sample weight in the laboratory. The data obtained were analyzed using the biomass estimation formula and carbon content and statistical equation to determine the difference in carbon content at each station. Results: From the results of the study obtained total carbon in station I was 3.498351 tons / ha, station II was 0.180750 tons / ha and station III was 16.727136 tons / ha. Conclusion: With the difference of each station based on the BNT Test with a confidence level of 99% showing the value of the difference of 20.58, while the BNT test of the confidence level of 95% shows the difference in value of 13.59.